Chromosomal translocations and karyotype complexity in chronic lymphocytic leukemia: A systematic reappraisal of classic cytogenetic data. Issue 3 (March 2014) - Baliakas, Panagiotis; Iskas, Michalis; Gardiner, Anne; Davis, Zadie; Plevova, Karla; Nguyen‐Khac, Florence; Malcikova, Jitka; Anagnostopoulos, Achilles; Glide, Sharron; Mould, Sarah; Stepanovska, Kristina; Brejcha, Martin; et al.
<x xml:space="preserve">Abstract</x> The significance of chromosomal translocations (CTRAs) and karyotype complexity (KC) in chronic lymphocytic leukemia (CLL) remains uncertain. To gain insight into these issues, we evaluated a series of 1001 CLL cases with reliable classic cytogenetic data obtained within 6 months from diagnosis before any treatment. Overall, 320 cases were found to carry ≥1 CTRAs. The most frequent chromosome breakpoints were 13q, followed by 14q, 18q, 17q, and 17p; notably, CTRAs involving chromosome 13q showed a wide spectrum of translocation partners. KC (≥3 aberrations) was detected in 157 cases and significantly (P < 0.005) associated with unmutated IGHV genes and aberrations of chromosome 17p. Furthermore, it was identified as an independent prognostic factor for shorter time‐to‐first‐treatment. CTRAs were assigned to two categories (i) CTRAs present in the context of KC, often with involvement of chromosome 17p aberrations, occurring mostly in CLL with unmutated IGHV genes; in such cases, we found that KC rather than the presence of CTRAs per se negatively impacts on survival; (ii) CTRAs in cases without KC, having limited if any impact on survival. On this evidence, we propose that all CTRAs in CLL are not equivalent but rather develop by different processes and are associated with distinct clonal behavior. Am. J. Hematol. 89:249–255, 2014. © 2013 Wiley Periodicals, Inc.